Gender Equality for a Thriving, Sustainable Arctic - Embla Eir Oddsdóttir; Hjalti Ómar Ágústsson; Eva-Maria Svensson; Gunhild Hoogensen Gjørv; Sarah Seabrook Kendall; Malgorzata (Gosia) Smieszek; Tahnee Prior; Erika Hayfield; Karla Jessen Williamson; Marya Rozanova-Smith; Andrey Petrov; Varvara Korkina Williams (Sustainability, 2021)
On 21 May 2021, a milestone Pan-Arctic Report: Gender Equality in the Arctic was published in tandem with the Arctic Council’s Ministerial Meeting held in Reykjavík, 19–20 May 2021. This article provides a brief review of the report and its major findings across six chapters that address key themes concerning gender equality in the Arctic: Law and Governance, Security, Gender and Environment, Migration and Mobility, Indigeneity, Gender, Violence, Reconciliation and Empowerment and Fate Control. A major conclusion of the report is that accessible, comparable, gender-disaggregated, and Arctic -specific data is severely lacking. Further, all chapters highlight the importance of gender-based analysis and gender mainstreaming in all decision-making processes at national and regional levels. The varying roles that gender—and its intersections with existing inequalities—plays in mediating the impacts of climate change and other socioeconomic transformations are also discussed throughout the report. The Arctic Council is identified as the main driver for implementing recommendations that were provided and discussed at the Council’s Ministerial Meeting and in the Reykjavík Declaration 2021, where the eight ministers of Arctic states “Emphasize[s] the importance of gender equality and respect for diversity for sustainable development in the Arctic… encourage[s] the mainstreaming of gender-based analysis in the work of the Arctic Council and call[s] for further action to advance gender equality in the Arctic”. This report and its policy relevant highlights, address these priorities and serve as a knowledge base for promoting gender equality and non-discrimination in the Arctic.